The impact of using an assistant device in learning the leap skill of the small background on parallel device for women - Ibrahim, Ismael (Journal of Physical Education, 2015)
The study aimed to identify the impact of the use of an Assistant Device (the device consists of two ropes. Each rope is 4 meters length. They are tied with safety belt around the student waist in order to learn the leap skill of the small background of parallel device for women. The researcher used the experimental method on a sample of students in the second stage in the college of Physical Education / Baghdad University for the study year 2013 – 2014. It has been randomly selected class H and choose 24 student through the method of lots. After excluding failed students and due to many absences, the total number for the final sample had become (20 students). The sample divided into two groups (the control group (10) students and the experimental group (10) students). The application method took (6) weeks at a rate of two educational units in two days (Tuesday and Thursday) a week and this is the number of units which are planned for the second phase of learning. The educational unit per time was (60 minutes) for both groups. The researcher adopted the vocabulary of education set by the supervisor to teach this skill to the two groups. The Assistant Device had been added to the method vocabulary of the members of the research sample. The researcher concluded that the effectiveness of the using the Assistant Device to learn the leap skill on parallel device with various heights. The researcher recommend the necessity to use the assistant device when teaching the leap skill on a parallel device with different heights and to be aware of the importance of the diversity of methods and the educational assistance tools that will help in learning the skills better and in correct way and its important role in the teaching process for the use of the right tool at the appropriate time and circumstances to keep students away from boredom situation during learning